2004
DOI: 10.1099/mic.0.26942-0
|View full text |Cite
|
Sign up to set email alerts
|

The hyaluronate lyase of Staphylococcus aureus – a virulence factor?

Abstract: The hyaluronate lyase (HL) gene of Staphylococcus aureus 8325-4 (hysA) was inactivated in vitro with the insertion of the erythromycin determinant, ermC, from plasmid pE194. The hysA : : ermC mutation was introduced into S. aureus via a temperature-sensitive shuttle vector, where it underwent homologous recombination with the wild-type (w.t.) allele. The insertion of ermC in the chromosomal hysA locus was confirmed by Southern blot hybridization and the loss of HL activity was demonstrated macroscopically by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
83
1
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(91 citation statements)
references
References 34 publications
6
83
1
1
Order By: Relevance
“…pyogenes parental strains were able to use HA as a sole source of carbon while hyaluronidase mutants were not. Others have also reported a role for hyaluronidase both in disease and in the acquisition of a suitable carbon and energy source (Cheng et al, 1995;Homer et al, 1997;Shain et al, 1996).In a previous study, hyaluronidase expression in S. aureus 8325-4 was shown to be activated by agr and repressed by sarA, as determined by hyaluronidase-specific activity in spent media (Makris et al, 2004). This study also showed that a mutation in the hyaluronidase gene resulted in reduced virulence in a mouse abscess model.…”
supporting
confidence: 57%
See 3 more Smart Citations
“…pyogenes parental strains were able to use HA as a sole source of carbon while hyaluronidase mutants were not. Others have also reported a role for hyaluronidase both in disease and in the acquisition of a suitable carbon and energy source (Cheng et al, 1995;Homer et al, 1997;Shain et al, 1996).In a previous study, hyaluronidase expression in S. aureus 8325-4 was shown to be activated by agr and repressed by sarA, as determined by hyaluronidase-specific activity in spent media (Makris et al, 2004). This study also showed that a mutation in the hyaluronidase gene resulted in reduced virulence in a mouse abscess model.…”
supporting
confidence: 57%
“…In a previous study, hyaluronidase expression in S. aureus 8325-4 was shown to be activated by agr and repressed by sarA, as determined by hyaluronidase-specific activity in spent media (Makris et al, 2004). This study also showed that a mutation in the hyaluronidase gene resulted in reduced virulence in a mouse abscess model.…”
Section: Introductionmentioning
confidence: 53%
See 2 more Smart Citations
“…(2009) 40:60hyaluronidase reflects increased hydrolysis of the extracellular matrix and enhanced permeability of the interstitial barrier for inflammatory cells. However, degradation of the interstitial barrier may also lead to a stronger infiltration of pathogens, possibly resulting in an increased immune response of the host [31]. Polymorphic neutrophil (PMN)-derived secretions of antibacterial enzymes such as serine proteases could cause the strong decline in the level of the elastase-sensitive protein SP-D which results in a decrease of the anti-inflammatory impact it has on the course of disease [9,48].…”
Section: Discussionmentioning
confidence: 99%